Parasitorliabditis fuchsi sp. n. (Nematoda, Rhabditidae) — паразит соснового лубоеда малого (Blastophagus minor Нагtig) - Блинова, С.Л.; Гурандо, Е.В. (Вестник зоологии, 1974)
Parasitic larvae of Parasitorhabditis fuchsi sp. n. are found in the Blastophagus minor H a r t i g. body cavity. The availability of two morphologically different generations of this species — parasitic and free-living one is established. Ontogenetic form formation and morphological variability of the new Nematoda species are studied. The description and drawings of the found Nematoda are given.